Sistem ANBK Dalam Meningkatkan Mutu Pendidikan Internal MAS Insan Kesuma Madani - Amiruddin Amiruddin; Uswatun Hasanah; Yulita Suyatmika; Retno Pringadi; Budi Setiawan Ginting (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study was conducted to determine the ANBK system in improving the quality of internal education of MAS Insan Kesuma Madani madrasah. From this objective, it can be seen that the ANBK system in the Madrasah improves the quality of internal education. This research was conducted using a qualitative approach. Data collection techniques in this study using interviews, observation and documentation. Data analysis was carried out using the stages of the Miles and Huberman model such as: (1) collecting data, (2) reducing data, (3) presenting data, (4) drawing conclusions. The main problem in this research is that there are still some obstacles in implementing ANBK in the madrasa. The findings and conclusions of the study show that first, madrasas have several obstacles in operating hardware such as operating servers, labtops and software. second, madrasas have encountered difficulties in socializing to students to operate the labtop during the covid 19 pandemic. Third, the difficulty of networking in madrasas because they are located in remote areas has an impact on comfort in implementing ANBK. Keywords : ANBK System, Internal Education Quality